2022
DOI: 10.2106/jbjs.oa.22.00053
|View full text |Cite
|
Sign up to set email alerts
|

Effective Mentorship of Women and Underrepresented Minorities in Orthopaedic Surgery

Abstract: Background: Orthopaedic surgery is currently the least diverse medical specialty, and there is little research on the mentorship needs for women and underrepresented minorities (URMs) in orthopaedics. The purpose of this study was to examine the roles and functions of mentorship for women and URMs in orthopaedic surgery, to understand mentorship preferences, and to elucidate barriers to mentorship in orthopaedic surgery. Methods: Members of J. Robert Gladden Orthopaedic Society and Ruth Jackson Orthopaedic Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Additionally, a lack of minority individuals among faculty has been perceived by program directors to be the greatest barrier to applications from minority groups 16 . Thus, increasing the visibility of race- or gender-concordant role models will lead to subsequent increases in diversity, but this also increases the mentoring burden on female and URM faculty 83 . However, role models do not have to be from underrepresented groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a lack of minority individuals among faculty has been perceived by program directors to be the greatest barrier to applications from minority groups 16 . Thus, increasing the visibility of race- or gender-concordant role models will lead to subsequent increases in diversity, but this also increases the mentoring burden on female and URM faculty 83 . However, role models do not have to be from underrepresented groups.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of orthopaedic residents, >90% saw having a role model in orthopaedics as a positive influence in their specialty selection, and more women (59%) than men (25%) cited having a role model of the same ethnicity or sex as a positive influence 50 . A separate study found that URM respondents were more likely than non-URM respondents to consider mentor-mentee race and/or ethnicity concordance to be important 83 . Research has demonstrated that female medical students attending institutions with greater gender diversity among faculty as well as URM students attending institutions with greater URM representation among faculty are more likely to apply for orthopaedic residency than those attending institutions with less diversity 23,84,85 .…”
Section: Role Models and Mentorshipmentioning
confidence: 98%
“…3,4 This includes spine surgery fellowship. 22 Exposure to and mentorship from URM faculty are instrumental for increasing the number of URM residents who pursue surgical careers. Several studies have found that URM representation among faculty is associated with an increased propensity of URMs to choose careers in academic medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Semistructured interviews were chosen over structured interviews because this format makes better use of the knowledge-producing potentials of dialog by allowing more leeway for following up on whatever angles are deemed important by the interviewee, increasing the richness of data 32 . He and other study team members have had past experience conducting qualitative research [33][34][35] . At the time of the study initiation, he was a current orthopaedic surgery resident (Post-Graduate Year [PGY]-3) within the program.…”
Section: Data Collectionmentioning
confidence: 99%